Simultaneous extraction and determination of mono-/polyglutamyl folates using high-performance liquid chromatography-tandem mass spectrometry and its applications in starchy crops - Wan, Xing; Han, Li-Da; Yang, Min; Zhang, Hong-Yang; Zhang, Chun-Yi; Hu, Ping (Analytical and bioanalytical chemistry, 2019)
Folates are typically present in polyglutamyl form in organisms. In traditional extraction methods, polyglutamyl folates are hydrolyzed to monoglutamates, sacrificing valuable information. To advance folate metabolism research, we developed an accurate, sensitive, and reproducible extraction method for polyglutamyl folate species in maize, the main crop in most parts of the world. Twelve folates, including six polyglutamyl folates, were simultaneously determined in maize for the first time using high-performance liquid chromatography-tandem mass spectrometry. The glutamation states of the folates were protected by boiling, which inactivated the native conjugases. α-Amylase and protease were added to obtain better recoveries and decrease difficulties in centrifugation and filtration. The recoveries ( n = 5 ) of six polyglutamyl folates were between 80.5 and 101%. All calibration curves showed good linear regression ( r 2 ≥ 0.994) within the working range. The instrumental limits of detection and quantitation ranged from 0.070 to 2.4 ng/mL and 0.22 to 8.0 ng/mL, respectively. Intra- and inter-day precision was below 7.81% and 11.9%, respectively ( n = 5 ). Using this method, changes in poly- and monoglutamyl folates during maize germination were determined for the first time. The results suggest that folates were largely synthesized as germination initiated, and 5-methyltetrahydrofolate was the most abundant species. Tetraglutamyl 5-methyltetrahydrofolate contributed more than 50% of the 5-methyltetrahydrofolate species. Inverse changes in contents of 5,10-methenyltetrahydrofolate, and 10-formyl folic acid, monoglutamate, and diglutamate of 5-formyltetrahydrofolate were also observed, indicating potential regulation. Additionally, polyglutamyl folates in sweet potatoes were determined using this method, indicating its applications in starchy crops.